Single‐ and Multiple‐Dose Pharmacokinetics and Pharmacodynamics of PN‐943, a Gastrointestinal‐Restricted Oral Peptide Antagonist of α4β7, in Healthy Volunteers. Issue 11 (4th May 2021) - Modi, Nishit B.; Cheng, Xiaoli; Mattheakis, Larry; Hwang, Ching‐Chang; Nawabi, Roya; Liu, David; Gupta, Suneel
Abstract: PN‐943 is an orally stable, gastrointestinal‐restricted peptide that binds specifically to α4ß7 integrin on leukocytes, blocking leukocyte trafficking to and activation in the gut, inhibiting colon inflammation and reducing signs and symptoms of active ulcerative colitis. Two pharmacokinetic/pharmacodynamic studies were conducted in healthy volunteers. Study 1 was a first‐in‐human study with 40 male subjects receiving PN‐943, 100 to 1400 mg or placebo, as single doses and 57 male subjects receiving PN‐943, 100 to 1000 mg or placebo, as multiple doses. Study 2 was a randomized, crossover study comparing multiple doses of 450‐mg PN‐943 twice daily as a liquid solution and as an immediate‐release tablet in 10 subjects. No subjects discontinued due to treatment‐emergent adverse events. Consistent with the gastrointestinal‐restricted nature of the peptide, systemic exposure was minimal; there was an approximate dose‐proportional increase in area under the plasma concentration–time curve. There was minimal accumulation with once‐daily dosing and an absence of time‐dependent changes in pharmacokinetics. Administration of PN‐943 after a high‐fat meal reduced peak plasma concentration and area under the plasma concentration–time curve. There was minimal (<0.1%) urinary excretion of intact drug, and there was a dose‐related increase in fecal excretion of intact PN‐943. Dose‐dependent increases in blood receptor occupancy and reduction in blood receptor expression were observed, supporting target engagement. Twice‐daily dosing resulted in sustained receptor occupancy with low plasma fluctuations (143%). PN‐943 was generally well tolerated following single and multiple oral doses with low systemic exposure. Twice‐daily dosing resulted in sustained pharmacokinetics and pharmacodynamics, supporting further investigation in efficacy studies.